A mechanistic insight into the bioaccesible herbometallic nanodrug as potential dual therapeutic agent. (September 2020) - Bera, Debbethi; Pal, Kunal; Ruidas, Bhuban; Mondal, Dheeraj; Pal, Shinjini; Paul, Biplab Kumar; Karmakar, Parimal; Das, Sukhen; Nandy, Papiya
Graphical abstract: Highlights: A successful synthesis and characterization of herbometallic nano drug, Vanga Bhasma nanoparticles (VBNPs). The antibacterial activity of VBNPs has been shown via standard method and techniques. VBNP induced oxidative damage in both eukaryotic and prokaryotic cells has been demonstrated successfully. Impairment of antioxidant levels (GSH, NADPH) and mitochondrial membrane disruptions in the presence of VBNPs. Programmed cell death or cell apoptosis induction establishes the anticancer efficacy of VBNPs. Abstract: Vanga Bhasma, a herbometallic mixture compound is used as gastrointestinal digestive medicine in ayurveda. Here, we have studied its bioaccessbility as antibacterial and anti cancer agent. Their characteristic FESEM, XRD, FTIR, UV absorption spectra were determined, which indicates high mineral content in Vanga Bhasma nanoparticles. Biological studies like MIC, MBC evaluate its antibacterial property, bacterial ROS generation enhance the ravages of peptidoglycan layer of bacterial cell wall. Further anti-cancerous potential of synthesized Vanga Bhasma nanoparticles was also studied on breast cancer cell line showing its potential to induce apoptosis through oxidative damage and mitochondrial membrane damage. Our studies thus successfully establish the dual therapeutic attribute of Vanga Bhasma nanoparticles as anticancer and antibacterial agent.